Intraoperative Colonic Irrigation for Low Rectal Resections With Primary Anastomosis: A Fail-Safe Surgical Model - Herzberg, Jonas; Khadem, Shahram; Guraya, Salman Yousuf; Strate, Tim; Honarpisheh, Human (Frontiers in Surgery, 2022)
Regardless the technological developments in surgery, the anastomotic leakage (AL) rate of low rectal anastomosis remains high. Though various perioperative protocols have been tested to reduce the risk for AL, there is no standard peri-operative management approach in rectal surgery. We aim to assess the short-term outcome of a multidisciplinary approach to reduce the rates of ALs using a fail-safe-model using preoperative and intraoperative colonic irrigation in low rectal resections with primary anastomosis. Between January 2015 and December 2020, 92 patients received low rectal resections for rectal cancer with primary anastomosis and diverting ileostomy. All these patients received pre-operative mechanical bowel preparation (MBP) without antibiotics as well as intraoperative colonic irrigation. The intraoperative colonic irrigation was performed via the efferent loop of the ileostomy. All data were analyzed by SPSS for descriptive and inferential analyses. In the study period, 1.987 colorectal surgical procedures were performed. This study reports AL in 3 (3.3%) of 92 recruited patients. Other postoperative complications (Dindo-Clavien I-IV) were reported in 25 patients (27.2%), which occurred mainly due to non-surgical reasons such as renal dysfunction and sepsis. According to the fail-safe model, AL was treated by endoscopic or re-do surgery. The median postoperative length of hospitalization was 8 days (4–45) days. This study validates the effectiveness of a multi-disciplinary fail-safe model with a pre-operative MBP and an intraoperative colonic irrigation in reducing AL rates. Intraoperative colonic irrigation is a feasible approach that lowers the AL rates by reducing fecal load and by decontamination of the colon and anastomotic region. Our study does not recommend a pre-operative administration of oral antibiotics for colorectal decontamination.